Fully biodegradable and mass-producible conductive fiber based on tungsten–poly(butylene adipate-co-terephthalate) composite - Yong-Wu Kim; Kyung-Sub Kim; Joo-Hyeon Park; Woo-Jin Lee; Jae-Young Bae; Seung-Kyun Kang (npj Flexible Electronics)
Abstract Biodegradable electronic fibers offer high flexibility, large surface area, and spatial deformability, enabling conformal tissue contact, efficient signal acquisition, and minimal invasiveness—ideal for sustainable and transient electronics. However, previously developed biodegradable conductive fibers often suffered from incomplete degradability, limited flexibility, and scalability. Here, we introduce a biodegradable, flexible, and mass-producible fiber electrode, consisting of tungsten microparticles, a polybutylene adipate-co-terephthalate matrix and a poly butanedithiol 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione pentenoic anhydride coating. The dry-jet wet-spinning process ensures uniform filler dispersion and continuous fiber formation, yielding high conductivity (~2500 S m−1) over lengths exceeding 10 m. The coating provides flexibility (~38% strain) and durability against repeated deformation and laundering. We demonstrate wearable textile electronics by integrating fiber-based temperature sensors, electromyography electrodes, and a wireless coil into an arm sleeve. Finally, enzymatic and soil biodegradation tests highlight their potential as sustainable and eco-friendly disposable electronics.